2013
DOI: 10.1111/1574-6968.12275
|View full text |Cite
|
Sign up to set email alerts
|

luxSin bacteria isolated from 25- to 40-million-year-old amber

Abstract: Interspecies bacterial communication is mediated by autoinducer-2, whose synthesis depends on luxS. Due to the apparent universality of luxS (present in over 40 bacterial species), it may have an ancient origin; however, no direct evidence is currently available. We amplified luxS in bacteria isolated from 25 to 40 million year-old amber. Phylogenies and Principal Component Analyses (PCA) of luxS and the 16S rRNA gene from ancient and extant bacteria were constructed. Amber isolates exhibited unique 16S rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Another field of research that has been revitalised by the introduction of NGS and hybridisation enrichment technologies is the study of ancient microbiota. DNA studies of ancient bacteria were highly controversial for many years , predominantly due to a lack of independent replication and authentication criteria, which would effectively screen for contamination from ubiquitous environmental microbes. More recent studies have shown that using both shotgun sequencing and hybridisation enrichment approaches it is possible to obtain (more) reliable genetic information from palaeopathogens .…”
Section: Data Interpretationmentioning
confidence: 99%
“…Another field of research that has been revitalised by the introduction of NGS and hybridisation enrichment technologies is the study of ancient microbiota. DNA studies of ancient bacteria were highly controversial for many years , predominantly due to a lack of independent replication and authentication criteria, which would effectively screen for contamination from ubiquitous environmental microbes. More recent studies have shown that using both shotgun sequencing and hybridisation enrichment approaches it is possible to obtain (more) reliable genetic information from palaeopathogens .…”
Section: Data Interpretationmentioning
confidence: 99%
“…have also been isolated from 23- to 35-million-year-old and 120-million-year-old amber, respectively (6163). Even more unexpected was the isolation of Gram-negative bacteria resembling Brevundimonas in 25- to 40-million-year-old amber (64). The isolation of a Gram-negative, non-spore-forming bacterium suggests that microbes have an array of currently unknown mechanisms that could be involved in their long-term survival.…”
Section: Sources Of Ancient Microbial Dnamentioning
confidence: 99%
“…Currently, the specific molecular mechanisms by which microbes isolated from amber become dormant and are resuscitated after millions of years are being further investigated. Amplification of genes such as rpf , which stands for resuscitation promoting factor, and luxS , a gene involved in quorum sensing, may suggest that genes identified in extant bacteria may be involved in the survival of ancient microorganisms, including those preserved in amber (63, 64). …”
Section: Sources Of Ancient Microbial Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…Although Santiago-Rodriguez et al (2014) attempt to reconstruct the evolutionary history of bacterial quorum sensing, the authors fail to address previous criticisms of this work and do not provide the appropriate experimental controls and analyses required to make the claims put forth in this article.…”
mentioning
confidence: 99%